Peran Aktif Mahasiswa KKN dalam Pengembangan Pendidikan di SDN 6 Telangkah - Ainni Ainni; Reza Nadia; Indah Setiawati; Husniah Husniah; Rabiah Al-Adawiyah; Raihan Nadhir; Muhammad Jumadin Noor; Mila Mila (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2024)
The Community Service Program (KKN) at SDN 6 Telangkah, Desa Hampalit, was chosen as a topic for community engagement due to the need for improving the quality of education. Given the challenges of access and quality in education, KKN serves as an important means to empower the community and integrate theory with practice. The method used is participatory, involving teachers, students, and staff at every stage of the activities, from problem identification to evaluation. Activities included the "Go Mengaji" program to enhance skills in reading the Al-Qur'an, cleanliness socialization through interactive approaches, and teaching various subjects. The results of the KKN implementation indicate a significant improvement in students' ability to read the Al-Qur'an/Iqra, higher motivation to learn due to the created murals, and increased awareness of the importance of cleanliness. Overall, the outcomes of KKN emphasize that community service can positively impact education and character development in students. Therefore, collaboration between academics and the community is crucial for creating a better learning environment, ensuring that quality education is accessible to all segments of society.